A CFD assisted segmented control volume based heat exchanger model for simulation of air-to-refrigerant heat exchanger with air flow mal-distribution. (25th February 2018) - Lee, Moon Soo; Li, Zhenning; Ling, Jiazhen; Aute, Vikrant
Highlights: Integrated CFD (OpenFOAM)-segmented HX model is developed for air mal-distribution. CFD model is validated with a PIV data from literature and showed good agreement. Parametric study shows HX angle has the most significant influence. Multivariate linear interpolation predicts air velocity profile very well very fast. Maximum relative L2 error norm is 5.8% for 5-variable interpolation. Abstract: Air flow mal-distribution has been identified as one of the causes for performance degradation of air-to-refrigerant heat exchangers. The accurate prediction of such a non-uniform air flow profile requires full heat exchanger simulations using Computational Fluid Dynamics (CFD) models which are often much more computationally expensive than traditional lumped parameters or finite volume based heat exchanger models. The high computational cost of CFD makes it difficult to comprehensively study the effect of multiple parameters impacting the air flow distribution and the heat exchanger performance. In this study, an integrated CFD-segmented heat exchanger model based on a momentum resistance model is developed that is computationally efficient and accurate. The CFD simulation process is fully automated using script based open-source CFD code, OpenFOAM. The momentum resistance-based CFD model is validated against Particle Image Velocimetry (PIV) data and parametric studies are performed to investigate the influence of heat exchanger geometries (HX angle, HX depth, HX height and fin type) and air flow rate on the air flow mal-distribution under dry operating condition. In addition, an approach to scale the velocity profiles using multivariate linear interpolation is proposed. The interpolation model can further accelerate the simulation speed without compromising the accuracy compared to the CFD model.